Preparation of kartogenin-loaded PLGA microspheres and a study of their drug release profiles - Chang, Hyun-Kyung; Koh, Yong-Gon; Hong, Hyoung-Taek; Kang, Kyoung-Tak (Frontiers in Materials, 2024)
Kartogenin, a potent inducer of chondrogenic differentiation in mesenchymal stem cells and a key agent in cartilage regeneration, presents a viable therapeutic strategy for osteoarthritis management. Despite the abundance of literature on therapeutic potential of kartogenin, there is a paucity of studies characterizing the formulation specifics in microsphere fabrication. This exploration is pivotal to advances in regenerative medicine, particularly in the domain of cartilage regeneration, to assure clinical efficacy and safety. In this work, we fabricated kartogenin-loaded PLGA microspheres with diverse formulations and their particle size, size distribution, encapsulation efficiency, drug loading and release profiles were characterized.Ratio of polymer, drug, and solvent and the use of surfactant was used as variables, and in particular, the effect of surfactant on particles was investigated. The average diameter of the spheres was 16.0-31.7 μm. Morphological variations from solid to porous surface structures depending on surfactant incorporation during the emulsification process was observed.Cumulative kartogenin release from microspheres ranged from 53.8% to 80.9% on day 28, and release profiles conform predominantly to the Korsmeyer-Peppas kinetics model. This study provides a foundational framework for modulating kartogenin release dynamics, a critical consideration for optimizing therapeutic efficacy and minimizing adverse effects in cartilage tissue engineering applications.